Clinical significance of CD13 and epithelial mesenchymal transition (EMT) markers in hepatocellular carcinoma. (14th November 2017) - Yamanaka, Chihiro; Wada, Hiroshi; Eguchi, Hidetoshi; Hatano, Hisanori; Gotoh, Kunihito; Noda, Takehiro; Yamada, Daisaku; Asaoka, Tadafumi; Kawamoto, Koichi; Nagano, Hiroaki; Doki, Yuichiro; Mori, Masaki
Abstract : The enrichment of CD13, a cancer stem cell marker, was correlated with early recurrences, and poor prognosis in patients with hepatocellular carcinoma. Abstract: Background & Aims: To improve prognosis in patients with hepatocellular carcinoma (HCC), the molecular mechanisms of tumor thrombus formation and metastasis must be clarified. The epithelial–mesenchymal transition (EMT) and cancer stem cells (CSCs) play crucial roles in tumor invasion and metastasis. This study aimed to reveal the clinical significance of the expression of the functional CSC marker, CD13, and investigate the correlation between CD13 expression and two EMT markers, E-cadherin and vimentin. Methods: We acquired clinical samples from 86 patients with HCC that underwent radical liver resections. We performed immunohistochemistry to evaluate CD13, E-cadherin and vimentin expression. We investigated the relationships among protein expression levels, clinicopathological factors and prognosis. Results: Based on CD13 expression, patients were categorized into CD13 high ( n = 30, 34.9%) and CD13 low ( n = 56, 65.1%) groups. The mean tumor size was significantly larger in the CD13 high group than in the CD13 low group ( P = 0.049). Compared with the CD13 low group, the CD13 high group showed significantly earlier recurrences and shorter survival times. In the multivariate analysis, CD13 high was an independent prognostic factor for overall survival (hazard ratio, 1.98; P = 0.044). The disease-free survival time was shorter in the vimentin-positive group than that in the vimentin-negative group ( P = 0.014). In an analysis of the relationship between CD13 and EMT, there was no significant correlation between CD13 and EMT markers. Conclusions: Our findings suggested that CD13 enrichment was correlated with early recurrences, and poor prognosis in patients with HCC and that vimentin was associated with early recurrences. CD13 represents a potential therapeutic target for HCC, because CSC regulation and EMT suppression are essential in cancer therapy.